2013
DOI: 10.1152/jn.00330.2013
|View full text |Cite
|
Sign up to set email alerts
|

α5GABAA receptors mediate primary afferent fiber tonic excitability in the turtle spinal cord

Abstract: γ-Amino butyric acid (GABA) plays a key role in the regulation of central nervous system by activating synaptic and extrasynaptic GABAA receptors. It is acknowledged that extrasynaptic GABAA receptors located in the soma, dendrites, and axons may be activated tonically by low extracellular GABA concentrations. The activation of these receptors produces a persistent conductance that can hyperpolarize or depolarize nerve cells depending on the Cl(-) equilibrium potential. In an in vitro preparation of the turtle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 56 publications
6
22
0
Order By: Relevance
“…7A/7B). As reported in turtles [41], there was α 5 -GABA A receptors immunoreactivity in DRG (Figs. 7C/7D) and peripheral afferent fibers of the rat (Figs.…”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…7A/7B). As reported in turtles [41], there was α 5 -GABA A receptors immunoreactivity in DRG (Figs. 7C/7D) and peripheral afferent fibers of the rat (Figs.…”
Section: Resultssupporting
confidence: 76%
“…Consistent with this hypothesis, we previously demonstrated that α 5 -GABA A receptor blockade leads to antinociception in the rat formalin test [11]. Notably, α 5 -GABA A receptors have been localized at the dorsal horn in mice and rats [43,53] and are also found in DRG and peripheral nerve fibers in turtles [41], making them well placed to modulate the nociceptive process. However, the role of α 5 -GABA A receptors in chronic inflammatory or neuropathic pain is unclear.…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations